PENGARUH KOMITMEN ORGANISASI DAN DAN ORGANIZATIONAL CITIZHENSHIP BEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN - Amsya, Akmal Huda Maulana; Alim, Syahirul (Universitas Bina Taruna Gorontalo, 2025)
This study aims to examine the influence of organizational commitment and Organizational Citizenship Behavior (OCB) on employee performance at PT Griya Sewu Berkah Pertiwi, Malang City. The background of this research is based on the importance of human resources who possess high commitment and positive organizational behavior in order to improve the effectiveness and productivity of companies, especially in the increasingly competitive property industry. This research uses a quantitative method with an associative approach. Data were collected through questionnaires distributed to 40 respondents who are active employees of the company. The data analysis technique employed is multiple linear regression. The results show that simultaneously, organizational commitment and OCB have a significant effect on employee performance. Partially, both organizational commitment and OCB also have a positive and significant impact on performance. These findings reinforce that the higher the level of organizational commitment and OCB, the better the employee performance. This research is expected to provide practical contributions for company management in efforts to improve employee performance by strengthening commitment and fostering a positive work culture.